Respuesta :

d = r*t  ⇒ t = d/r

Third choice

Answer:

t = d/r

Step-by-step explanation:

In order to solve an equation for another term from which is initally solved by another term you just have to leave the term you want to solve the equation for, in this case the "t" and to do so since in this formula it is multiplying the "r" we haec to divide both sides of the equation by "r":

[tex]d=rt[/tex]

[tex]\frac{d}{r} =\frac{rt}{r}[/tex]

Now we eliminate the since they are in both sides of the fraction:

[tex]\frac{d}{r} =\frac{rt}{r}[/tex]

And the function is solved for t.

[tex]t=\frac{d}{r}[/tex]

ACCESS MORE